Vietnam : photographies et éthique du souvenir - Debary, Octave (Ciel variable)

(untitled) (Les Productions Ciel variable, 2005)
Abstract What meaning should be given to the commemoration of the thirtieth anniversary of the fall of Saigon? This text analyzes how Souvenirs du Vietnam, a work by Liza Nguyen, offers a photographic aesthetic that is reminiscent of an ethics of remembrance. Surfaces recomposes scatterings of land and colours, all of which speak directly of absence. Mirroring Surfaces, Cartes postales du Vietnam invites us to look at history in its most banal form: tourism. Here, are we disturbed by the horror of these images or by the horror of their distanced point of view? It is in the limits to the representative power of the image - never reached -that an immateriality that forms the basis for the real work of remembering positively emerges.